Rancang Bangun Alat Monitoring Energi Listrik Pada Kulkas Berbasis Smartphone - Qoriatul Fitriyah; Tri Vira Putri; Aditya Wirangga; Muhammad Prihadi Eko Wahyudi (JURNAL INTEGRASI, 2021)
Electric energy monitoring device on smartphone-based refrigerators are intended as part of an energy saving campaign. This device works with the principle of regulating the power of the refrigerator based on the parameters of the temperature and starting time of the refrigerator. If the temperature has stabilized, the refrigerator will automatically turned off so that electrical energy consumption can be reduced. This device is also connected to an Android-based application so that the device's performance can also be regulated via mobile phones with certain variables.